The clinical impact of malnutrition on the postoperative outcomes of patients undergoing colorectal resection surgery for colon or rectal cancer: Propensity score matched analysis of 2011–2017 US hospitals. (September 2021) - Lee, David Uihwan; Fan, Gregory Hongyuan; Hastie, David Jeffrey; Addonizio, Elyse Ann; Suh, Julie; Prakasam, Vibhav Narayan; Karagozian, Raffi
Abstract: Background & aims: Malnutrition can be prevalently found in patients with significant-to-advanced colorectal cancer, who potential require colorectal resection procedures; to accurately describe the postoperative risks, we used a propensity-score matched comparison of national database to analyze the effects of malnutrition on post-colectomy outcomes. Methods: 2011–2017 National inpatient Sample was used to isolate inpatient ceases of colorectal resection procedures, which were stratified using malnutrition into malnutrition-present cohort and malnutrition-absent controls; the controls were propensity-score matched with the study cohort using 1:1 ratio and compared to the following endpoints: mortality, length of stay, costs, postoperative complications. Results: After matching, there were 11357 with and without malnutrition who underwent colorectal resection surgery; in comparison, malnourished patients had higher rates of in-hospital mortality (6.14 vs 3.22% p < 0.001, OR 1.96 95%CI 1.73–2.23), length of stay (15.4 vs 9.61d p < 0.001), costs (163, 962 vs 102, 709 p < 0.001), and were more likely to be discharged to non-routine discharges, including short term hospitals, skilled nursing facilities, and home healthcare. In terms of complications, malnourished patients had higher bleeding (2.87 vs 1.68% p < 0.001, OR 1.73 95%CI 1.44–2.07), wound complications (4.31 vs 1.34% p < 0.001, OR 3.32 95%CI 2.76–3.99), infection (6 vs 2.62% p < 0.001, OR 2.38 95%CI 2.07–2.73), and postoperative respiratory failure (7.27 vs 3.37% p < 0.001, OR 2.25 95%CI 1.99–2.54). Conclusion: This study demonstrates the presence of malnutrition to be associated with adverse postoperative outcomes including mortality and complications in patients undergoing colorectal resection surgery for colon cancer. Highlights: Patients with colorectal cancers may suffer from malnutrition due to cancer-driven metabolic dysregulation. We evaluate the impact of malnutrition on post-colorectal surgery outcomes using a propensity score-matched analysis of a national database. The study shows clinical malnutrition to be associated with postoperative mortality, longer stay, higher costs, and surgical complications. The findings suggest the use of nutrition therapy in pre/postoperative settings in order to optimize surgical outcomes in malnourished patients.